LIVING WELL DYING WELL: PUTTING THESE WORDS INTO ACTION. Issue 2 (1st June 2013) - Larpent, Andrew; Davidson-Park, B; McCallum, S; Price, K; Evans, D; Ullrich, S; Williamson, P
Abstract : Background: Providing quality end of life care in residential aged care (RAC) is influenced by multiple drivers including the workforce to deliver care. Older Australians rank palliative care and dying with dignity as major issues requiring future aged care workforce reform. Aim: This presentation will outline the new workforce model to be developed through the Living Well Dying Well project. Key objectives and examples of case studies will illustrate how: To implement a targeted education programme that focuses on all staff at Southern Cross Care. To create a better workforce balance. To harness a cultural shift amongst all involved to establish a partnership approach. To build leadership for change and sustainability of the new workforce model. To provide quality end of life care in RAC. Methods: Outcome Mapping is being used as a change management tool and a developmental evaluation methodology to assist Southern Cross Care to successfully implement the Living Well Dying Well project. It ensures a logical, participatory and reflective set of steps so as to address the complexity of the project in the context of RAC. Results: The project is currently in development stage therefore this presentation will focus on the change management process, the 'End of Life' model of service delivery that is underpinning the workforce reform and challenges along the way. Discussion: The project is possible due to funding by Health Workforce Australia. It is ensuring positive and open attitudes towards death and dying to enable all residents and their families the choice and dignity that is integral to living well and dying well in RAC. Conclusion: At Southern Cross Care we are thinking more systematically and pragmatically about how our workforce provide advance care planning and end of life care. We are already translating our thinking about how to do it, to bring about the desired outcomes, into action.